Seni Pertunjukan Kuda Kepang Abadi di Desa Tanjung Morawa A, Medan - Sumatera Utara - Inggit Prastiawan (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2014)
This research focuses on the ‘plaited horse dance’ Abadi Performing Arts in Tanjung Morawa A, Medan City North Sumatra, which is still alive, although it has been too long and too far from the origin. The horse dance has passed down by the descant of Javanese which have lived in North Sumatra for several generations. As common sense that the performing art has spread widely to several region out of Indonesia brought by Javanese people as migrant such as in Malaysia, Suriname, Hongkong, Japan, and United States of America. It is considered as one of Javanese arts which brought by Javanese wherever we live in line with their migration purposes area. Javanese community overseas, usually still hold the horse dance performing art for event related to the human cycle of life, including as part of their ritual ceremony or merely such entertainment for the people. In 1st suro (muharram, the first month in islamic calendar) commemoration, the horse dance performing art usually also staged.